Work-Related Musculoskeletal Disorders and Mental Health among Nursing Personnel in the Context of COVID-19 Pandemic in West Bengal, India - Chowdhury, Upasana; Das, Tamal; Mazumder, Sahana; Gangopadhyay, Somnath (International Journal of Occupational Safety and Health, 2023)
Introduction: COVID-19 outbreak created enormous turmoil all over the world. The health sectors were overburdened with critically ill COVID-19 patients. The load on the health sector burdened and fatigued the health care workers especially the nursing personnel as they were in direct contact with the symptomatic patients predominantly. In each wave, the patients’ number surged and overwhelmed the health sectors. In this study, the prevalence of work-related musculoskeletal disorders (WMSDs) discomfort and mental exhaustion among the nursing personnel were assessed. Methods: The duration of the study was from the end of September 2021 to March 2022. The factors that sourced the discomfort symptoms amidst and the interludes of the later waves of COVID-19 and their interrelations were also assessed here. The Modified Nordic Questionnaire and the COVID Stress Scales (CSS) were used in this study. Results: 73.9% of subjects (N=88) reported the presence of WMSDs symptoms in at least one body region in the last one-year time period with the most prevalent discomfort in the lower back region (42%), followed by discomforts in the ankles, neck, and knee. The mean value of the total score of CSS was 33.74(±19.90) with high mean values in compulsive checking, danger, and contamination subscales. This study showed significant positive correlations between the presence of WMSD symptoms with BMI (rs=0.266, p= 0.012) and CSS total scores (rs=0.216, p=0.043). Conclusion: Large percentages of reports on musculoskeletal discomforts with reports on mental enervation related to COVID-19 indicated weariness of the nursing personnel. The physical exhaustion due to overloading work and the interplay between mental stress and WMSDs revealed pivotal issues of concern.